2022
DOI: 10.3390/ijms23031841
|View full text |Cite
|
Sign up to set email alerts
|

3D Printable Composite Biomaterials Based on GelMA and Hydroxyapatite Powders Doped with Cerium Ions for Bone Tissue Regeneration

Abstract: The main objective was to produce 3D printable hydrogels based on GelMA and hydroxyapatite doped with cerium ions with potential application in bone regeneration. The first part of the study regards the substitution of Ca2+ ions from hydroxyapatite structure with cerium ions (Ca10-xCex(PO4)6(OH)2, xCe = 0.1, 0.3, 0.5). The second part followed the selection of the optimal concentration of HAp doped, which will ensure GelMA-based scaffolds with good biocompatibility, viability and cell proliferation. The third … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…We also emphasize the key factors that govern the functional vascularization of GelMA-based vascular constructs after transplantation in vivo . Potential topics that we briefly mentioned but are worth further investigation are the development of visible light-based photocrosslinking systems ( Noshadi et al, 2017 ; Sharifi et al, 2021 ) and the advances in the GelMA-based composite materials ( Kurian et al, 2021 ; Alexa et al, 2022 ; Liang et al, 2022 ). In addition, research efforts will continue on the multiplex functionalities of GelMA-based biomaterials.…”
Section: Discussionmentioning
confidence: 99%
“…We also emphasize the key factors that govern the functional vascularization of GelMA-based vascular constructs after transplantation in vivo . Potential topics that we briefly mentioned but are worth further investigation are the development of visible light-based photocrosslinking systems ( Noshadi et al, 2017 ; Sharifi et al, 2021 ) and the advances in the GelMA-based composite materials ( Kurian et al, 2021 ; Alexa et al, 2022 ; Liang et al, 2022 ). In addition, research efforts will continue on the multiplex functionalities of GelMA-based biomaterials.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, broader and less intense peaks can be detected with higher concentrations when techniques such as sol-gel and the microwave irradiation method are used. These changes express a decrease in crystallinity and smaller crystallites [ 25 , 26 , 30 , 31 , 41 , 42 , 43 , 44 , 45 ]. In the case of Ce(IV)-HAp, Paduraru et al observed similar changes through the variation of the ion concentration from 0 to 10% [ 27 ].…”
Section: Impact Of Lanthanide Incorporation On the Morphology And Pro...mentioning
confidence: 99%
“…After 14 days of osteogenesis induction, there was a significant increase in the expression of OSX. After 28 days, higher OPN expression was registered [ 45 ].…”
Section: Biomedical Applications Of Lanthanides-substituted Hapmentioning
confidence: 99%
“…It has been reported that nHA has a chemical composition similar to that of natural bone tissue, which can promote osteoblasts adhesion and has good biocompatibility and osteogenic induction activity. nHA implantation can facilitate new bone formation through the chemical bonding between its surface charge and the host bone, 37,38 which therefore allows the preservation of the host bone stock and promotes the integration of the prosthesis with the bone, thereby reducing long-term prosthesis loosening rate. 39 In the presented study, the interfaces between the bone and stem were all wellosseointegrated, as evaluated by T-SMART, and all implanted endoprostheses survived without aseptic loosening.…”
Section: F I G U R Ementioning
confidence: 99%